2018
DOI: 10.1007/s10096-018-3265-z
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and CXCL10 responses related to complaints in patients with Q fever fatigue syndrome

Abstract: Approximately 20% of patients with acute Q fever develop Q fever fatigue syndrome (QFS), a debilitating fatigue syndrome. This study further investigates the role of C. burnetii-specific IFNγ, but also IL-2, CXCL9, CXCL10, and CXLC11 production in QFS patients. C. burnetii-specific IFNy, IL-2, CXCL9, CXCL10, and CXCL11 production were tested in ex vivo stimulated whole blood of QFS patients who recovered from their complaints (n = 8), QFS patients with persisting complaints (n = 27), and asymptomatic Q fever s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The biological factors in PCC, such as immune activation, might be the result of a conditioning mechanism by chronic stress in addition to the SARS-COV-2 infection. Our findings share similarities with observations made in PIFS: Higher IFN gamma production was observed in Q fever fatigue syndrome patients after ex vivo stimulation of whole blood with Coxiella burnetti , but there was no correlation between these findings and the level of fatigue or symptom duration [ 73 ]. The clinical overlap between PCC and PIFS could mean that gene expression correlates are shared independent of the infectious trigger.…”
Section: Discussionsupporting
confidence: 89%
“…The biological factors in PCC, such as immune activation, might be the result of a conditioning mechanism by chronic stress in addition to the SARS-COV-2 infection. Our findings share similarities with observations made in PIFS: Higher IFN gamma production was observed in Q fever fatigue syndrome patients after ex vivo stimulation of whole blood with Coxiella burnetti , but there was no correlation between these findings and the level of fatigue or symptom duration [ 73 ]. The clinical overlap between PCC and PIFS could mean that gene expression correlates are shared independent of the infectious trigger.…”
Section: Discussionsupporting
confidence: 89%
“…First reports supporting this notion came from Penttilla et al in 1998, who showed that peripheral blood mononuclear cells (PBMCs) of QFS patients produce more IL-6 when stimulated with Q fever antigen than controls [ 11 ]. During the Dutch Q fever outbreak (2007–2010), our group demonstrated that QFS patients exhibit signs of altered immunity through the monocyte-derived cytokines Tumor Necrosis Factor (TNF)α, interleukin (IL)-1β, and especially IL-6, together with the interferon (IFN)γ-axis [ 12 14 ]. In addition, we found that monocytes of both QFS and CFS patients show decreased expression of mitochondrial derived peptide (MDP)-coding genes MT-RNR1 and MT-RNR2 , resulting in a decreased production of humanin ( MT-RNR2 ) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…First reports supporting this notion came from Pentilla et al in 1998, who showed that peripheral blood mononuclear cells (PBMCs) of QFS patients produce more IL-6 when stimulated with Q fever antigen than controls (11). During the Dutch Q fever outbreak (2009-2012), our group demonstrated that QFS patients exhibit signs of altered immunity through the monocyte-derived cytokines Tumor Necrosis Factor (TNF)α, interleukin (IL)-1β, and especially IL-6, together with the interferon (IFN)γ-axis (12)(13)(14). In addition, we found that monocytes of both QFS patients and CFS patients show decreased expression of mitochondrial derived peptide (MDP)-coding genes MT-RNR1 and MT-RNR2, resulting in a decreased production of humanin (MT-RNR2) (15).…”
Section: Discussionmentioning
confidence: 88%